Above-threshold ionization of diatomic molecules by few-cycle laser pulses - Gazibegović-Busuladžić, A.; Hasović, E.; Busuladžić, M.; Milošević, D. B.; Kelkensberg, F.; Siu, W. K.; Vrakking, M. J. J.; Lépine, F.; Sansone, G.; Nisoli, M.; Znakovskaya, I.; Kling, M. F. (My University, 2011)
Above-threshold ionization of diatomic molecules by infrared carrier-envelope phase (CEP) stable few-cycle laser pulses is analyzed both experimentally and theoretically. The theoretical approach is based on the recently developed molecular improved strong-field approximation (ISFA), generalized to few-cycle pulses. Instead of using the first Born approximation, the rescattering matrix element in the ISFA is now calculated exactly. This modification leads to the appearance of characteristic minima in the differential cross section as a function of the scattering angle. Experimental angle-resolved photoelectron spectra of N2 and O2 molecules are obtained using the velocity map imaging technique. A relatively good agreement of experimental and simulated angle-resolved spectra, CEP-dependent asymmetry maps, and extracted electron-molecular ion elastic scattering differential cross sections is obtained.